ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN - Ayu Rizqi Sani, 09.05.52.0143; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2013)
The study was conducted to analyze the effect of Return on Assets (ROA), Return on Equity (ROE), Current Ratio (CR), Price Earning Ratio (PER), and Size of theFirm Value. The object of this thesis is the LQ-45 company that listed on the Indonesia Stock Exchange (BEI) in 2009-2011. The data analysis is multiple linear regression with the least squares equation. Test for normality showed that the data were normally distributed research. Multicollinearity test, heteroscedasticity test, and autocorrelation test in the classical assumption that the variableis not found to deviate. This shows the available data has been qualified using multiple linear regression equation models. During the observation period oft esting hypotheses using t-statistics for testing the partial regression coefficients and F-statistics to test the significance influences together. The results of this study indicate that the variab le CR showed no significant effect on PBV. ROA and Size variable hasa significant negative effecton PBV. Variable ROE and PER significant positive effect onPBV. Predictive ability of the four variables toPBV in this studyby 86.4% while the remaining 13.6% influenced by other factors not included in the research model Keywords: ROA, ROE, CR, PER, PBV.